2009
DOI: 10.1007/s12010-008-8515-6
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent Chromium Reduction by Free and Immobilized Cell-free Extract of Arthrobacter rhombi-RE

Abstract: In the present study, hexavalent chromium (Cr(VI)) reduction potential of chromium reductase associated with the cell-free extracts (CFE) of Arthrobacter rhombi-RE species was evaluated. Arthrobacter rhombi-RE, an efficient Cr(VI) reducing bacterium, was enriched and isolated from a chromium-contaminated site. Chromium reductase activity of Arthrobacter rhombi-RE strain was associated with the cell-free extract and the contribution of extracellular enzymes to Cr(VI) reduction was negligible. NADH enhanced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 37 publications
1
39
0
1
Order By: Relevance
“…In a recent work, chromate reductases associated with cell-free extracts of A. rhombi-RE were immobilized with different matrices and calcium alginate beads proved to be most effective (Elangovan et al 2010). However, the performance was not encouraging under continuous mode of operation (Table 2).…”
Section: Purification and Characterization Of Bacterial Chromate Redumentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent work, chromate reductases associated with cell-free extracts of A. rhombi-RE were immobilized with different matrices and calcium alginate beads proved to be most effective (Elangovan et al 2010). However, the performance was not encouraging under continuous mode of operation (Table 2).…”
Section: Purification and Characterization Of Bacterial Chromate Redumentioning
confidence: 97%
“…These compact convex patches are organic components stimulated by CrO 4 2- (Yang et al 2007). Elangovan et al (2010) Hence, an over expression of extracellular biological components for preventing the permeability of CrO 4 2-into the cell helps the bacteria to survive chromate stress.…”
Section: Bacterial Cr(vi) Resistancementioning
confidence: 99%
“…Studies have shown that certain species of bacteria, mixed bacterial cultures, yeast, algae, and fungi are able to transform Cr(VI) to the trivalent form Cr(III), which is less toxic and mobile Desai et al 2008;Lee et al 2008;Molokwane et al 2008;Okeke et al 2008;Bankar et al 2009;Kong et al 2009;Quintelas et al 2009;Sanghi and Sankararamakrishnan 2009;Ahmad et al 2010;Elangovan et al 2010;Fernández et al 2010;Orozco et al 2010;Dalcin et al 2011;Ilias et al 2011;Orozco et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…4). Significant increase in the rate of Cr(VI) reduction by the addition of an exogenous electron donor such as glucose or glycerol has been observed in several Cr(VI) reducing bacteria such as Enterobacter cloacae ), Arthrobacter rhombi (Elangovan et al 2010), Pseudomonas aeruginosa (Ganguli et al 2002), Bacillus stearothermophilus (Manolov et al 1995), etc.…”
Section: Effect Of Electron Donormentioning
confidence: 99%
“…have been used for Cr reduction and proved to be effective. These immobilized cells being more stable, can be reused and are easy to regenerate with easier solid-liquid separation (Humphries et al 2005;Elangovan et al 2010). Under immobilized conditions, cells are protected against the excessive toxic action of high chromate concentration and thereby improve the cellular activities compared with free cells.…”
Section: Introductionmentioning
confidence: 99%